Factors Creating an Educational Atmosphere in Cyberspace: A Qualitative Study - Aeen Mohammadi; Mandana Shirazi; Atekeh Mousavi; Rita Mojtahedzadeh (Kerman University of Medical Sciences, 2017)
Background Because of the developments and advancements in information technology (IT), unparalleled opportunities have been provided in electronic arenas; among them, electronic learning (e-learning) systems have brought attention to the facilitation of education. Since educational environment is a factor influencing the success of educational programs, the current study aims at evaluating the factors that create the educational atmosphere in cyberspace. Methods The current study employed a qualitative content analysis approach and a targeted sampling method. A total of 11 students and 13 faculty members were recruited by a semi-structured interview in 2015. The interviews were continued separately for both students and lecturers up to the saturation of sample size. After the interview data were qualitatively analyzed. Results After the data analysis, 685 codes were extracted out of the qualitative data, which were reevaluated in several stages and classified into 38 subcategories. Then, 13 categories and 6 domains (The status of virtual education, learner support, teaching skills, evaluation, professionalism and professional ethics, and self-efficacy) were created. Conclusions Since the educational environment is an inseparable part of a curriculum, the factors creating an educational atmosphere in cyberspace are critically important and necessary for the qualitative and quantitative evaluations of the curriculum and prediction of educational outcomes.